Impact assessment of municipal wastes on the ecological state of ukraine - Трофімов, Ігор Леонідович (Eastern-European Journal of Enterprise Technologies, 2014)
The problem of assessing the impact of municipal wastes on the ecological state of Ukraine, and the ways of its solution are given. The main purpose of the research was to assess the impact of pollution sources of municipal solid wastes on the environment, and to justify the effective recycling of municipal wastes. The impact of SMW pollution sources on the environment state was assessed. The negative impact of wastes on the environment of Ukraine was studied. The problem of solid municipal waste management in Ukraine and in the world was analyzed. It was found that incineration and landfilling of solid municipal wastes are inefficient technologies today as they do not solve the energy problem in the country because they do not allow to obtain alternative energy sources from wastes, as well as they have a negative impact on the ecological state of Ukraine. It was proved that the most effective way to reduce emissions of biogas (landfill gas) from solid municipal waste landfills into the atmosphere − is to collect and use it. Economic indicators of production projects and the use of landfill gas are cost-effective enough, especially when waste landfill is placed near industrial gas consumer. The research results can be applied in the field of ecology and environmental protection. The research results can be applied by ecologists, as well as power engineers and chemmotology experts in the establishment and management of alternative energy sources.